Impact of environmental barriers on temnospondyl biogeography and dispersal during the Middle–Late Triassic - Moreno, Raphael; Dunne, Emma; Mujal, Eudald; Farnsworth, Alexander; Valdes, Paul J.; Schoch, Rainer R. (Palaeontology, 2024)
Temnospondyls had a remarkable worldwide distribution throughout the Triassic at a time of periodic arid climates, and were a stable component of Triassic terrestrial ecosystems. Given the postulated ancestral relationship between temnospondyls and modern lissamphibians it is pertinent to recognize that the group may have exhibited some degree of ecological resilience and adaptability. Despite this higher level of plasticity, temnospondyls might still have been susceptible to environmental and climate changes. Although fossil sites are distributed sporadically, we try to circumvent the present geographical and geological biases by combining actual fossil occurrences with environmental conditions derived from general circulation models. Here, we employ species distribution modelling to examine the palaeogeographic and palaeoclimatic distribution of European temnospondyls during the transition from Middle to Late Triassic. The model shows different suitable areas for temnospondyl habitats that give new potential insights on the biogeographic distribution patterns and dispersal potential. We suggest that the Central European Basin functioned as a focal point for Triassic temnospondyl diversification and spread. Moreover, this paper provides the first application of species distribution modelling for Triassic temnospondyls and aids in understanding their climatic niche occupation and evolution.
CRIS-Team Scopus Importer:2024-09-13
Keywords: biogeography; palaeobiology; palaeoclimate; species distribution model; Temnospondyli; Triassic